Iatrogenic vas deferens injuries: Neglected infertility causing traumas - Ali Shalizar Jalali (Babol University of Medical Sciences, 2017)
116 Iatrogenic vas deferens injuries (IVDIs) as inadvertently medical conditions are critical complications of surgical operations in the inguinal region of children and adults. It is well documented that any scant disturbance in vas deferens tunica muscularis or mucosa will endanger fertility and unintentionally manipulations during inguinal hernia repair can cause perforation and/or obstruction of damaged vas deferens resulting in male fertility reduction. It has also been suggested that IVDIs can play crucial roles in formation of anti-sperm autoantibodies and sympathetic vasospasm leading to bilateral testicular deterioration as well as sperm motility and capacitation impairments. In line with that, it seems that non-recognized IVDIs may have destructive effects on spermatogenesis resulting in fertility problems and careful attention to surgical detail should be considered during inguinal region surgical procedures to prevent IVDIs. However, recent progresses in urological microsurgeries and assisted reproductive technologies provide remarkable improvements in fertility outcomes of patients even with serious iatrogenic reduction in fertility.